2019
DOI: 10.33073/pjm-2019-050
|View full text |Cite
|
Sign up to set email alerts
|

The Composition of Fungal Communities in the Rumen of Gayals (Bos frontalis), Yaks (Bos grunniens), and Yunnan and Tibetan Yellow Cattle (Bos taurs)

Abstract: The rumen is a microbial-rich ecosystem in which rumen fungi play an important role in the feed digestion of ruminants. The composition of rumen fungi in free-range ruminants such as gayals, yaks, Tibetan yellow cattle, and the domesticated Yunnan yellow cattle was investigated by sequencing an internal transcribed spacer region 1 (ITS1) using Illumina MiSeq. A total of 285 092 optimized sequences and 904 operational taxonomic units (OTUs) were obtained from the four cattle breeds. The rumen fungi abundance an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 48 publications
3
9
0
Order By: Relevance
“…More than 90% of fungi sequences isolated in the rumen remain unclassified [54], however, the presence of anaerobic fungi belonging to phylum Neocallimastigomycetes (genera Neocallimastix, Caecomyces, Piromyces, Anaeromyces, Orpinomyces, and Cyllamyces) is acknowledged [55]. Fungi are infrequently found in strained rumen fluid because zoospores attach and colonize (encyst and germinate to produce the fungal thallus) the plant fragments suspended in the rumen natural digesta, being only then released by the sporangia [56].…”
Section: Fungimentioning
confidence: 99%
“…More than 90% of fungi sequences isolated in the rumen remain unclassified [54], however, the presence of anaerobic fungi belonging to phylum Neocallimastigomycetes (genera Neocallimastix, Caecomyces, Piromyces, Anaeromyces, Orpinomyces, and Cyllamyces) is acknowledged [55]. Fungi are infrequently found in strained rumen fluid because zoospores attach and colonize (encyst and germinate to produce the fungal thallus) the plant fragments suspended in the rumen natural digesta, being only then released by the sporangia [56].…”
Section: Fungimentioning
confidence: 99%
“…We identified eight distinct genera of the phylum Neocallimastigomycetes, including Neocallimastix, Caecomyces, Piromyces, Anaeromyces, Orpinomyces, Cyllamyces , and Buwchfawromyces in over 80% of the ruminal samples collected from steers on both baseline and alfalfa pasture. Studies using ITS1 primer sets different than the one used in the present study have reported recovery of less than 23% of the sequencing reads assigned to ARF [ 19 ] and identified fewer ARF genera, including Piromyces, Anaeromyces, Cyllamyces, Neocallimastix , Caecomyces, and Orpionmyces [ 19 , 42 ]. By using a similar primer set to our study, Kumar et al [ 22 ] reported recovery of around 1% of the sequencing reads belonging to ARF and identified three genera within this phylum, including Cyllamyces, Caecomyces, and Orpinomyces .…”
Section: Discussionmentioning
confidence: 90%
“…Currently, ARF are classified into 18 distinct genera belonging to the phylum Neocallimastigomycota [18]. Among these, Neocallimastix, Piromyces, Caecomyces, Cyllamyces, Orpinomyces, Anaeromyces, Pecoramyces, and Buwchfawromyces have been previously identified in the rumen and fecal contents of cattle using a combination of culture-dependent and marker-gene sequencing methodologies [19][20][21][22][23]. These genera can be distinguished by morphological features, or through genetic variations in the internal transcribed spacer (ITS) region of the ribosomal RNA (rRNA) locus [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…The reason for this inconsistent pattern in the relative abundance of Acetitomaculum is uncertain and requires further research. Studies have demonstrated that there are substantial differences in rumen microbial structure and diversity between yaks and cattle ( An et al, 2005 ; Huang et al, 2012 ; Wang et al, 2019b ). Therefore, there are differences in the utilization of nutrient substrates between bovine species and different relationships may be formed between the host and microorganisms.…”
Section: Discussionmentioning
confidence: 99%